2014
DOI: 10.1080/13614533.2014.914960
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Influential Decision Making Factors for University Library Opening Hours: An Exploratory UK Regional Study

Abstract: Many factors and pressures affect decisions made in UK university libraries on opening hours especially 24/7. This article reports on a project to examine the decision making process, influential factors, and stakeholders. A workshop for senior library managers in theEast Midlands was held to gather data and share experiences. From analysis of the workshop a framework of influential factors was devised and the decision making process was examined. Although each library had different priorities, important facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…This question was important as during the first phase of this research the workshop participants had indicated this was a particularly influential factor. Most of the factors revealed in this study reinforce the findings from the previous regional workshop based study by Ravenwood et al (2015), highlighting the relevance of these findings to the academic library sector. Unsurprisingly, demand from undergraduates was the most influential and this is further explored in the next section.…”
Section: Influential Factorssupporting
confidence: 86%
See 4 more Smart Citations
“…This question was important as during the first phase of this research the workshop participants had indicated this was a particularly influential factor. Most of the factors revealed in this study reinforce the findings from the previous regional workshop based study by Ravenwood et al (2015), highlighting the relevance of these findings to the academic library sector. Unsurprisingly, demand from undergraduates was the most influential and this is further explored in the next section.…”
Section: Influential Factorssupporting
confidence: 86%
“…The overall picture of twenty four hour opening was complicated by different patterns of opening throughout the academic year and different patterns at multiple libraries within a University, reflecting findings from previous studies (Laaker 2011;Ravenwood, Stephens and Walton 2015). Forty five percent of respondents reported opening 24/7 for at least part of the year, though only 11% had 24/7 opening throughout the whole year.…”
Section: Twenty Four Hour Openingsupporting
confidence: 62%
See 3 more Smart Citations